Susan Pinkard: A Revolution in Taste: The Rise of French Cuisine - Lehmann, Gilly (Petits Propos Culinaires, 2009)
Susan Pinkard: A Revolution in Taste: The Rise of French Cuisine: New York: Cambridge UP: 2009, hardback: ISBN 9780521821995: xv–317pp., $32